The minimum inhibitory concentration and exposure time of the combination of quaternary ammonium compound with ethylendiamintetraacetic acid (EDTA) against methicillin-resistant Staphylococcus Aureus - Dwirayunita, Swasty (Padjadjaran Journal of Dentistry, 2009)
The aim of this study was to determine The Minimum Inhibitory Concentration (MIC) and the exposure time of the combination of quaternary ammonium compound with ethylenediaminetetraacetic acid (EDTA) towards Methicillin-resistant Staphylococcus aureus so that the combination can be applied as a disinfectant against MRSA.The tested bacteria MRSA was isolated from the RSGM of the Faculty of Dentistry Padjadjaran University. This laboratory experimental study was conducted based on a serial dilution method. The combination of quaternary ammonium compound with EDTA was diluted in 1/1000, 1/2000, 1/4000, 1/8000, 1/16000, 1/32000, 1/64000, and 1/128000 concentration.The result showed that the combination of quaternary ammonium compound with EDTA inhibited the MRSA on 1/1000, 1/2000 and 1/4000 concentrations. The effective exposure time to reduce the number of MRSA colonies are 2.5 and 3 minutes with 1/1000 concentration from the combination. In conclusion that the MIC of the combination of quaternary ammonium compound with EDTA is in 1/4000 concentration and the effective exposure time is more than 3 minutes.